A COMPARISON OF SEVERAL STOCHASTIC TECHNIQUES FOR COMPUTATION OF MULTIDIMENSIONAL INTEGRALS: A COMPARISON OF SEVERAL STOCHASTIC TECHNIQUES FOR COMPUTATION OF MULTIDIMENSIONAL INTEGRALS - Todorov, Venelin; Dzhurov, Valerij; Tzvetkov, Ilian (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
A comprehensive experimental study based on Sobol sequence, Importance Sampling and Fibonacci based lattice rule has been done. This is the first time the Sobol sequence has been compared with the Importance sampling method for the problem under consideration. The numerical tests show that the stochastic algorithms under consideration are efficient tool for computing multidimensional integrals. In order to obtain a more accurate and reliable interpretation of the results this is very important.